2006
DOI: 10.1016/j.nuclcard.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 180° and 360° acquisition for myocardial perfusion SPECT with compensation for attenuation, detector response, and scatter: Monte Carlo and mathematical observer results

Abstract: With optimized reconstruction and filtering parameters, 180 degrees acquisition provided a statistically significant improvement over 360 degrees acquisition for FBP reconstruction. However, for OS-EM the differences were small and not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The results of this study are convergent with previous studies, which have compared the effect of new reconstruction methods on the image quality with shortened acquisitions [5,6,[16][17][18][19][20][21][22]. All these studies showed that the half-time acquisition together with the new reconstruction methods produced better image quality than the full-time acquisition with the standard reconstruction methods.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study are convergent with previous studies, which have compared the effect of new reconstruction methods on the image quality with shortened acquisitions [5,6,[16][17][18][19][20][21][22]. All these studies showed that the half-time acquisition together with the new reconstruction methods produced better image quality than the full-time acquisition with the standard reconstruction methods.…”
Section: Discussionsupporting
confidence: 88%
“…All these studies showed that the half-time acquisition together with the new reconstruction methods produced better image quality than the full-time acquisition with the standard reconstruction methods. Few of these studies used attenuation correction [6,21,22], but most concentrated only on collimator compensation [16][17][18][19][20]. To achieve the best possible lesion detection performance, all the corrections should be included in the reconstruction process, and therefore half-time imaging should also be evaluated with all the corrections.…”
Section: Discussionmentioning
confidence: 99%
“…Since 180-degree acquisition is preferable with FBP and comparable results are obtained with IR using 180-degree and 360-degree acquisitions (with correction for patient attenuation, detector response characteristics, and radiation scatter), 180-degree acquisition is recommended. 29 Some of the newer, unconventional radiation detector designs, especially those that employ arrays of small solid state detectors, 30 have the equivalent of many more ''heads'' than two-detector or three-detector gamma cameras. The potential for these newer SPECT systems to reduce radiation dose are discussed below.…”
Section: Imaging Systemsmentioning
confidence: 99%
“…A large number of images with known truth is needed to provide reliable estimates of these quantities (Fukunaga and Hayes, 1989a, Kupinski et al, 2007, Ge et al, 2014). Furthermore, in large optimization and evaluation studies, task performance is assessed for many different combinations of system parameters and methods, such as different collimator designs (Yihuan et al, 2014, Ghaly et al, 2016), reconstruction methods and parameters (Frey et al, 2002, Gilland et al, 2006, He et al, 2006), and post-reconstruction filters and processing techniques (Frey et al, 2002, Sankaran et al, 2002). Thus, ensemble techniques require an enormous number of images to be obtained and stored; which often limits the number of parameters that can be explored.…”
Section: Introductionmentioning
confidence: 99%
“…This could help in studying a larger number of parameters. The evaluation was performed in the context of optimizing the post-reconstruction filter cut-off frequencies for myocardial perfusion SPECT defect detection (He et al, 2006, Frey et al, 2002, He et al, 2004). In particular, we compared the CHO, CLD and CQD (Fukunaga, 1990).…”
Section: Introductionmentioning
confidence: 99%